Pseudogap-induced anisotropic suppression of electronic Raman response in cuprate superconductors. (4th May 2017) - Jing, Pengfei; Liu, Yiqun; Zhao, Huaisong; Kuang, Lülin; Feng, Shiping
Abstract : It has become clear that the anomalous properties of cuprate superconductors are intimately related to the formation of a pseudogap. Within the framework of the kinetic-energy-driven superconducting mechanism, the effect of the pseudogap on the electronic Raman response (ERR) of cuprate superconductors in the superconducting-state is studied by taking into account the interplay between the superconducting gap and pseudogap. It is shown that the low-energy spectra almost rise as the cube of energy in the channel and linearly with energy in the channel. It is also shown that the pseudogap is strongly anisotropic in momentum space, where the magnitude of the pseudogap around the nodes is smaller than that around the antinodes, which leads to that the low-energy spectral weight of the spectrum is suppressed heavily by the pseudogap, while the pseudogap has a more modest effect on the ERR in the orientation.